THE ROLE OF TEACHING ENGLISH IN COMPUTER-MEDIATED COMMUNICATION - Dilnoza Kdirbaeva (Journals Park Publishing, 2023)
The article is devoted to find the curiosity of English language in computer-mediated communication. Furthermore, the work gives fully understanding about the merits of computer-mediated communication in learning process.
Keywords: Computer-mediated communication, speech software, lingua Franca, web-based forums, computer mind-set, self-access, umbrella term, human error, error analysis.